Women’s Voices in Tiffany Reisz’s The Night Mark - Heri Dwi Santoso (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Tiffany Reisz's The Night Mark (2017) is an American time travel novel that talks about women issues, besides the time travel story itself. This study aims at describing women's voices in the novel. The theory used in this study is liberal feminism. The study finds out that there are several manifestations of voices of women different era about their lives, roles, and status both in the domestic area and within the society. It is concluded that the women's voices in the novel are in line with the spirit of liberal feminism, especially in how to see women's lives, roles, and status.